PENGEMBANGAN SUPLEMEN BAHAN AJAR IPAS MENGUBAH BENTUK ENERGI KELAS IV SDN 36 PONTIANAK SELATAN - Husnani, Nurmi; Hartoyo, Agung; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
According to experts in design, materials, language, and education, as well as students and teachers, the primary goal of the research was to create a product that could be used as a supplemental science lesson plan for the "Changing Forms of Energy" unit in fourth grade public elementary schools. A research and development approach that has been adapted from 4-D is used in this research. Among the three validators participating in the study, design experts achieved a 96% success rate with the "Highly Valid" criterion, material experts achieved a 90% success rate, and language experts achieved a 90% success rate through validation. The results of the development trial activities confirmed these findings; The first teacher's response was rated "Very Good" by 98% of students, while the second teacher's response was rated "Very Good" by 94% of students. The proportion of students meeting the "Excellent" standard on the student response exam was 93%. According to the results, fourth graders were eager to learn more about the supplemental science curriculum. Therefore, additional science lesson plans are practical to use in the classroom.